FOSTERING PRODUCTIVE LANGUAGE SKILLS IN ENGLISH FOR SPECIFIC PURPOSES (ESP) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
Developing learners’ productive language skills such as speaking and writing—is essential in English for Specific Purposes (ESP) settings, where communication needs are shaped by professional or academic goals. This research investigates how these skills are taught and practiced in ESP classrooms. Data from classroom observations and teacher interviews reveal that contextualized tasks and authentic materials play a significant role in improving learners' performance. The study underscores the importance of aligning instructional strategies with real-life communicative functions relevant to specific fields.